Molecular Mechanism Of Acute Phase Response : Identification Of Signal Transduction Pathways Mediating Cytokine Inhibitory Effect On Human Peroxisome Proliferator Activated Receptor Alpha (PPARa) In Liver Cells - Chew , Guat Siew (2010)
Cytokines, like IL-6, play an important role in triggering the acute phase response (APR) of the body to injury and inflammation. The dynamics of expression and interaction of the IL-6 signalling pathway components in the regulation of peroxisome proliferator-activated receptor alpha (PPARα) during APR remain to be properly identified. In this study, we determined that three possible potential signaling pathways, JAK-STAT, PI3K and MAPK (p38 and ERK1/2) which derived from the upstream JAK and SHP2 components of the IL-6 signalling were involved in IL-6-inhibitory effect on PPARα gene expression.